Urchin-like magnetic microspheres for cancer therapy through synergistic effect of mechanical force, photothermal and photodynamic effects - Wu, Kai; Mohsin, Ali; Zaman, Waqas Qamar; Zhang, Zefei; Guan, Wenyan; Chu, Maoquan; Zhuang, Yingping; Guo, Meijin (Journal of nanobiotechnology, 2022)
Magnetic materials mediated by mechanical forces to combat cancer cells are currently attracting attention. Firstly, the magnetic force penetrates deeper into tissues than the NIR laser alone to destroy tumours. Secondly, the synergistic effect of nano-magnetic-material characteristics results in a viable option for the targeted killing of cancer cells. Therefore, mechanical force (MF) produced by magnetic nanomaterials under low frequency dynamic magnetic field combined with laser technology is the most effective, safe and efficient tool for killing cancer cells and tumour growth. In this study, we synthesized novel urchin-like hollow magnetic microspheres (UHMMs) composed of superparamagnetic Fe O . We demonstrated the excellent performance of UHMMs for killing laryngocarcinoma cancer cells through mechanical force and photothermal effects under a vibrating magnetic field and near-infrared laser, respectively. The killing efficiency was further improved after loading the synthesised UHMMs with Chlorin e6 relative to unloaded UHMMs. Additionally, in animal experiments, laryngocarcinoma solid tumour growth was effectively inhibited by UHMMs@Ce6 through magneto-mechanic force, photothermal and photodynamic therapy. The biocompatibility and high efficiency of multimodal integrated therapy with the UHMMs prepared in this work provide new insights for developing novel nano therapy and drug loading platforms for tumour treatment. In vivo experiments further demonstrated that UHMMs/Ce6 are excellent tools for strongly inhibiting tumour growth through the above-mentioned characteristic effects.